Pengaruh Penerapan Hukuman Mati Terhadap Pelaku Tindak Pidana Narkotika - Johan Pardamean Simanjuntak; Chairun Nisa; Reh Bungana Br. PA; Maulana Ibrahim (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The aim of this research is to find out how the death penalty is applied to perpetrators of narcotics crimes in Indonesia and how the treatment of foreign nationals who commit narcotics crimes and/or Narcotics Precursor crimes, using normative legal research methods, is concluded. The application of the death penalty is part of law enforcement efforts, because if narcotics are not controlled and supervised strictly and thoroughly and are contrary to the provisions of the law, they will constitute a criminal act and cause great harm and danger. Narcotics crimes are transnational in nature and are carried out using high-level modus operandi. Therefore, it is necessary to apply the death penalty, life imprisonment, imprisonment and fines. Treatment of foreigners who commit narcotics crimes and/or narcotics precursor crimes must be expelled from the territory of the Unitary State of the Republic of Indonesia and prohibited from re-entering the territory of the Unitary State of the Republic of Indonesia.